2007
DOI: 10.1016/j.placenta.2006.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Potential Role of Peroxisome Proliferator-Activated Receptor γ in the Placenta of Diabetic Pregnancy

Abstract: Peroxisome proliferator-activated receptor gamma (PPARgamma) is expressed predominantly in adipose tissue and is known to be involved in adipocyte differentiation and insulin sensitivity. Recent reports indicated that PPARgamma-deficient mice were embryonic lethal due to abnormal placental development, suggesting that PPARgamma plays an important role in normal development of placenta. On the other hand, expression of vascular endothelial growth factor (VEGF), the other important factor in placental developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
2
27
1
1
Order By: Relevance
“…34 However, although PPAR-␥ agonists have been shown previously to restore proangiogenic factors, upregulate HO-1, 10 and increase the production of VEGF in vitro [35][36][37] and in vivo, 18 rosiglitazone failed to alter angiogenic factors in the RUPP rat in the present study. A recent study, involving the induction of HO-1 in RUPP rats via the administration of cobalt (III) protoporphyrin IX chloride, demonstrated that, as a result of cobalt (III) protoporphyrin IX chloride treatment, placental expression of HO-1 was increased, and there was a significant shift in the angiostatic balance ratio (sFlt-1:VEGF).…”
Section: Discussioncontrasting
confidence: 69%
“…34 However, although PPAR-␥ agonists have been shown previously to restore proangiogenic factors, upregulate HO-1, 10 and increase the production of VEGF in vitro [35][36][37] and in vivo, 18 rosiglitazone failed to alter angiogenic factors in the RUPP rat in the present study. A recent study, involving the induction of HO-1 in RUPP rats via the administration of cobalt (III) protoporphyrin IX chloride, demonstrated that, as a result of cobalt (III) protoporphyrin IX chloride treatment, placental expression of HO-1 was increased, and there was a significant shift in the angiostatic balance ratio (sFlt-1:VEGF).…”
Section: Discussioncontrasting
confidence: 69%
“…PPAR-g agonists have been shown to up-regulate HO-1 expression an anti-oxidant enzyme that negatively regulates the production of the anti-angiogenic mediator, sFlt-1 (Cudmore et al, 2007;Kronke et al, 2007). Moreover PPAR-g agonists serve to increase the production of the pro-angiogenic hormone, VEGF, in macrophages, vascular smooth muscle cells and endothelial cells (Jozkowicz et al, 2000;Yamakawa et al, 2000;Inoue et al, 2001a,b;Negro et al, 2005;Suwaki et al, 2007).…”
Section: Vasculoprotective Effects Of Ppar-gmentioning
confidence: 99%
“…24) PPARg protein expression significantly increased in diabetic mouse placentas as compared with in normal placenta, while, PPARg ligand attenuated the significantly enhanced PPARg expression at high glucose condition. 25) But high glucose caused both PPARa mRNA and protein expression reductions in islets or INS (832/13) bcells. 26) Berberine inhibited lipid synthesis in human hepatocytes not only through elevation the low density lipoprotein receptor expression, 27) but also through the activation of AMP-activated protein kinase (AMPK).…”
Section: Fig 7 Effects Of Drugs On Ppard Expression In Livermentioning
confidence: 99%